Morphosemantic features in Universal Grammar: What we can learn from Marshallese pronouns and demonstratives. (September 2022) - Cowper, Elizabeth; Hall, Daniel Currie
Abstract: This article analyzes Marshallese pronouns and demonstratives, arguing that both privative and binary morphosemantic features are necessary, and that the two types coexist in a single domain. Marshallese encodes number with atomic, and person with [ ± author] and [ ± participant]. In the complex system of Marshallese demonstratives, atomic and [ ± human] map to the same head, subject to a constraint that only one feature appears at a time. The element χ, which derives person orientation in demonstratives and pronouns, does not universally map to the same syntactic position. While in Heiltsuk χ is a dependent of the person head, in Marshallese it heads a projection above the person head. And while in Heiltsuk the person features occupy the same position in both pronouns and demonstratives, Marshallese pronouns have a different structure, with person and number features mapping to a single syntactic head. The contribution of UG is thus not a set of specific features or specific structures, but a set of more abstract principles.